2002
DOI: 10.1002/eej.10030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical performance simulation of frozen helium plasma disk MHD generator

Abstract: SUMMARYMHD electrical power generation with frozen helium plasma (FHP) is examined numerically. The FHP can be initiated by preionized helium without the alkali metal seed at the generator inlet. Since the three-body recombination coefficient of helium ions is low at electron temperatures above 5000 K, the ionization degree can be kept almost constant in the entire region of the generator channel. The r-θ two-dimensional numerical results show that the performance of the FHP MHD generator is comparable to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…On the other hand, in the recent years, studies have been done on seed‐free generation . Major methods of seed‐free generation are based on high‐temperature inert gas plasma and pre‐ionized inert gas plasma (frozen inert gas plasma) .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, in the recent years, studies have been done on seed‐free generation . Major methods of seed‐free generation are based on high‐temperature inert gas plasma and pre‐ionized inert gas plasma (frozen inert gas plasma) .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the recent years, studies have been done on seed‐free generation . Major methods of seed‐free generation are based on high‐temperature inert gas plasma and pre‐ionized inert gas plasma (frozen inert gas plasma) . With high‐temperature inert gas plasma, generation is performed through thermal equilibrium plasma obtained when inlet total temperature reaches about 9000 K. Experiments and numerical simulations using a shock tube showed that plasma becomes nonuniform because of ionization instability at a low inlet total temperature ( = low inlet ionization degree), and generated output is low; however, at a high inlet total temperature ( = high inlet ionization degree), ionization instability is suppressed, and output increases so that generation performance becomes comparable with that of seeded‐plasma generation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations